STUDI PALEOSEISMOLOGI AKIBAT BENCANA GEMPA BUMI DI ZONA SESAR KALIGARANG (KGFZ) DI SEMARANG - Fahrudin Fahrudin (Diponegoro University, 2013)
Earthquake in the past can study with paleoseismology. Kaligarang fault zone will record the event ofearthquake and result the sediment. The metode of research is detail field mapping and field excavation.Evidence of paleoseismology in the filed, we find the sand boil and carbon materials. We find two location ofsand boil near with reverse faults. Sand boil to precipitate at unit B Kalibeng Formation. Phase tectonic tocause earthquake occure at late Miocene – Early Pliocene.